If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 6 + -2x Solving 12 = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 12 + 2x = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 12 + 2x = 6 + 0 12 + 2x = 6 Add '-12' to each side of the equation. 12 + -12 + 2x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 6 + -12 2x = 6 + -12 Combine like terms: 6 + -12 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 1-3x=-10 | | (-3)-2y=9 | | 9a^2+27a=0 | | c(c-6)=27 | | 4.4Y+6.2=8.8Y-1.8 | | 42j+18-19j=-28-4c | | 5t-11=24 | | 3x=-3x | | 3n-5n-1=11-n | | 72n^4-168n^2+98=0 | | 12x^2+50=0 | | 7a+3a+2a-a=16 | | x^2+6xy+9y=0 | | 5x+9+2x-5= | | 2(x-1)-4(x+2)=8 | | 10x-26+5x-30=x^2 | | 9x^4-81x^2=0 | | 4/5(x+5)=7/8(3x+23)-7 | | 2(2n-3)=(7n+4)+2 | | 5(x+1)+2(x-3)=13 | | 10x+10=10x+10 | | (-2)=4x^2-2x-25 | | 15x-56x=x^2 | | 4-.025x=.1-.05x | | 3x^2-13x+4= | | 3x+8-5x=12 | | 4x^2+8x-35=0 | | 2+3x=9x-34 | | -18=-2/5(15n-45) | | x+7=x+4 | | 3(x+5)+4(x-3)=17 | | .3x-5.5=.2x+2.6 |